Underwater noise propagation models and its application in renewable energy parks: WaveRoller Case Study - Rocha, Adriana Andrade Sousa (2017)
In the light of global warming, large-scale transition to renewable power sources is a worldwide challenge, playing wind power a significant role. Sea wave energy is being increasingly regarded in many countries as a major and promising resource but, like all forms of energy conversion, it will inevitably have an impact on the marine environment. WaveRoller, a Wave Energy Conversion Device, is installed in front of Almagreira beach, on the west coast of Portugal. The purpose of this thesis is to study and quantify the underwater radiated noise from this device using an underwater acoustic model in order to estimate potential effects it may have in the marine environment. The model used to run the data will be MIKE Zero – Underwater Acoustic Simulator by DHI . In the study site only cetacean species are expected to occur. Results showed that behavioural responses might be expected for low and mid-frequency cetaceans if they swim close to the device. Also, the device shouldn’t be installed in an area in which a population of cetaceans exists in a 28m ray. For these individuals, injury can be assumed if SEL (Sound Exposure Level) is higher than 215 dB re 1μPa2.s, for non-pulse sounds. Results showed the calculated maximum SEL of the Waveroller sound is 150 dB re 1μPa2.s and therefore no injury is expected. MIKE Zero – Underwater Acoustic Simulator is a powerful tool to test any device that produces underwater noise and offers the possibility to create Surface Sound maps of results by using MIKEXYZ Converter tool.